Robust Stability of Fractional Order Memristive BAM Neural Networks with Mixed and Additive Time Varying Delays - Xiuping Han; M. Hymavathi; Sumaya Sanober; Bhawna Dhupia; M. Syed Ali (Fractal and Fractional, 2022)
This paper is concerned with the problem of the robust stability of fractional-order memristive bidirectional associative memory (BAM) neural networks. Based on Lyapunov theory, fractional-order differential inequalities and linear matrix inequalities (LMI) are applied to obtain a robust asymptotical stability. Finally, numerical examples are presented.